2011
DOI: 10.5339/qmj.2011.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Extramedullary Plasmacytoma of the Larynx Presenting with Stridor as a Primary Manifestation

Abstract: More than 90% of malignant tumors of the larynx are squamous cell carcinomas. Extramedullary plasmacytoma is a plasma cell tumour representing less than 1 % of all head and neck malignancies and involvement of the larynx is very rare. In the larynx the supraglottis is the primary site of involvement compared to the glottic and subglottic regions. We report a case of 54-yearold Indonesian female who presented at our clinic with stridor as primary manifestation secondary to solitary extramedullar plasmacytoma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, about 30%-50% of patients can progress to MM in a mean period ranging from 1.5 to 2.5 years (7). Statistical results vary from study to study (2)(3)(4)(5)(6)(7)(8)(9)(10), but the overall results appear to be compatible. Since 30%-50% of the patients progress to MM, it is critical to determine statistically significant risk factors and define practicable dose guidelines for radiation therapy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, about 30%-50% of patients can progress to MM in a mean period ranging from 1.5 to 2.5 years (7). Statistical results vary from study to study (2)(3)(4)(5)(6)(7)(8)(9)(10), but the overall results appear to be compatible. Since 30%-50% of the patients progress to MM, it is critical to determine statistically significant risk factors and define practicable dose guidelines for radiation therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Radiation therapy is currently the first line of treatment, with a local control rate reaching up to 90%. It has been reported that the 10-year disease-free and overall-survival rates range from 50% to 80%, and fewer than 10% of patients have local recurrence (2)(3)(4)(5)(6)(7)(8)(9)(10). However, about 30%-50% of patients can progress to MM in a mean period ranging from 1.5 to 2.5 years (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation